Design Evaluation on Sound Absorption Performance of Coconut Husk added with Pineapple Leaf Panel - Mahzan, Shahruddin; Awang Harun, Habib Haikal (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This paper compares the sound-absorbing properties of two different design panels of natural fibre composites with different compositions. Pineapple leaf and coconut coir fibres are used to make the composite panel. Sound absorption is evaluated with two different pane design iterations and various compositions of each fibre in a specimen. The test makes use of a simple impedance tube and two microphones. The transfer function of the two microphones in the frequency range of 0 Hz to 6000 Hz is used to compute the sound absorption coefficient. The volume fibres varied from 20 wt. %, 25 wt. %, and 30 wt. % while the polyurethane foam is 50 wt. % and is glued together to form a panel. The result shows that the sound absorption coefficient is directly proportional to the composition of pineapple fibre in the composite. This shows that pineapple fibre absorbs sound better than coconut husk fibre. It was also demonstrated that the design panel with holes has a better sound absorption coefficient compared to the plain design. The highest sound absorption coefficient recorded for the design with holes is 0.92, whereas the plain design recorded a 0.91 for its absorption coefficient